2020
DOI: 10.1111/phn.12782
|View full text |Cite
|
Sign up to set email alerts
|

Self‐collection of samples for HPV testing to increase participation in cervical cancer screening by immigrant women: An integrative review

Abstract: Objective To examine methods and results of studies assessing self‐collection of cervico‐vaginal samples for human papillomavirus (HPV) testing by immigrant women for insights into how future research using this method with unique subpopulations of women may improve the rates of cervical cancer screening (CCS) compared to current strategies. Data Sources Four electronic databases were systematically searched through March 2020, with no limits applied. A manual review of reference lists was also completed. Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Muslim culture was cited and rightly associated by our participants with a reduced likelihood of being up to date with cervical cancer screening [ 43 ]. Both interviews and focus groups validated the idea of accompanying certain immigrant women in screening education and offering appropriate support in follow-up to reduce disparities [ 44 ]. Level of education strongly influences the use of screening, with more highly educated women more likely to undergo it regularly [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Muslim culture was cited and rightly associated by our participants with a reduced likelihood of being up to date with cervical cancer screening [ 43 ]. Both interviews and focus groups validated the idea of accompanying certain immigrant women in screening education and offering appropriate support in follow-up to reduce disparities [ 44 ]. Level of education strongly influences the use of screening, with more highly educated women more likely to undergo it regularly [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results suggest that less than half of the women had heard of the screening test in their home countries (48.6%). Previous studies reported that lack of concept of screening in home countries may be one of the reasons for lower knowledge and uptake of screening in immigrants ( Vahabi and Lofters, 2016 , Mullins et al., 2014 , Elmore et al., 2020 ). Thus a need for including cervical screening education and support among other health care services for newly arriving immigrants can't be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…Given the cultural background, modesty and reluctance towards cervical screening, self-sampling could potentially increase South Asian women's screening uptake ( Marlow et al., 2015 , Vahabi and Lofters, 2016 , Mullins et al., 2014 ). However, self-sampling directions need to be clear and easy to follow, taking into account the potential for language barriers and reservations women may hold against this method such as inability to perform test accurately or belief that it could lead to self harm ( Elmore et al., 2020 , Howard et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…14,15 We can do this by assessing our migrant and refugee patients' need for culturally tailored education around prevention and screening for cervical cancer, and by continuing to research novel ways of increasing screening for this vulnerable population. 16,17 Although this brief report focuses only on cervical cancer control, it may also serve as a bellwether for increased awareness about disparities related to other cancers and noncommunicable diseases for refugee populations.…”
Section: Discussionmentioning
confidence: 99%